Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada Kantor Camat Palibelo - Zaitun Nisa; Sri Ernawati; Nur Khusnul Hamidah (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This study aims to examine the influence of work discipline and work motivation on employee performance at the Palibelo District Office. The research is based on the issue of low motivation and discipline among employees, which affects their performance. The study employs an associative quantitative approach. The population consists of 48 employees, all of whom were used as the sample through a saturated sampling technique. Data were collected using questionnaires and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and F-test. The results show that both work discipline and motivation have a significant partial effect on employee performance. Simultaneously, the two variables also significantly influence performance. The coefficient of determination indicates that work discipline and motivation contribute 44.45% to employee performance, while the remaining 55.55% is influenced by other unexamined variables. The study recommends enhancing discipline and motivation through the enforcement of firm regulations and the creation of a supportive work environment.